Development of Independence as an Effort to Improve Welfare for Convicts in Correctional Technical Implementation Units in Indonesia - Vivi Sylviani Biafri (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
The Directorate General of Corrections has the task of guiding and fostering convicts. Prisons and detention centers carry out this task. Self-reliance development is grouped into agribusiness, manufacturing, and service activities. Prisoners who participate in independent development activities are expected to have the provision after being released to find a job or be self-employed. By working, the welfare level of prisoners increases. The method used is qualitative. The research question posed is how is the implementation of fostering independence to increase the welfare of convicts and the obstacles encountered in independent activities and when free convicts want to get a job? This study aims to find out the implementation of self-reliance coaching to increase the welfare of convicts and the obstacles faced by independent activities. The problems convict face when looking for work or entrepreneurship. The results showed that several obstacles were found, such as inadequate infrastructure, non-specific activity budgets, low employee ability for E-commerce, low motivation of prisoners to participate in activities, and when free from prisoners, it is also difficult to get a job. The complexity of the problems faced must be overcome immediately, and it requires the involvement of all parties. One solution to help prisoners who need funds to become self-employed is through productive Zakat.